Regulation of the MDM2‐p53 pathway by the ubiquitin ligase HERC2 - García‐Cano, Jesús (Mol Oncol, 2019)
The p53 tumor suppressor protein is a transcription factor that plays a prominent role in protecting cells from malignant transformation. Protein levels of p53 and its transcriptional activity are tightly regulated by the ubiquitin E3 ligase MDM2, the gene expression of which is transcriptionally regulated by p53 in a negative feedback loop. The p53 protein is transcriptionally active as a tetramer, and this oligomerization state is modulated by a complex formed by NEURL4 and the ubiquitin E3 ligase HERC2. Here, we report that MDM2 forms a complex with oligomeric p53, HERC2, and NEURL4. HERC2 knockdown results in a decline in MDM2 protein levels without affecting its protein stability, as it reduces its mRNA expression by inhibition of its promoter activation. DNA damage induced by bleomycin dissociates MDM2 from the p53/HERC2/NEURL4 complex and increases the phosphorylation and acetylation of oligomeric p53 bound to HERC2 and NEURL4. Moreover, the MDM2 promoter, which contains p53‐response elements, competes with HERC2 for binding of oligomeric, phosphorylated and acetylated p53. We integrate these findings in a model showing the pivotal role of HERC2 in p53‐MDM2 loop regulation. Altogether, these new insights in p53 pathway regulation are of great interest in cancer and may provide new therapeutic targets.